2023
DOI: 10.3390/ijms241914771
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic Acid Alleviates Neuroinflammation after Intracerebral Hemorrhage by Mediating Microglial Pyroptosis via the NF-κB/NLRP3/GSDMD Pathway

Pan Lei,
Zhiyang Li,
Qiuwei Hua
et al.

Abstract: The neuroinflammatory response after intracerebral hemorrhage (ICH) causes a large amount of neuronal loss, and inhibiting the inflammatory response can improve the prognosis. In previous laboratory studies and clinical trials, ursolic acid (UA) inhibited the inflammatory response, but whether it can be administered to inhibit the neuroinflammatory response after cerebral hemorrhage is unknown. The aim of this study was to investigate the effects of ursolic acid after cerebral hemorrhage. Online databases were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…This is consistent with the current findings, which show that, when compared to the PTZ group, the groups pretreated with either the aerial part or the root extract of Z. album showed a significant inhibition in the NLRP3 inflammasome pathway and significantly downregulated NLRP3 , TXNIP and caspase-1 expression, along with reduced levels of IL-1β and IL-18. Indeed, NLRP3 inflammasome inactivation has been reported to be a potential mechanism of action of various compounds found in Z. album extract [ 71 , 72 , 73 , 74 , 75 ]. A better outcome has been observed with aerial part extract than the root extract.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the current findings, which show that, when compared to the PTZ group, the groups pretreated with either the aerial part or the root extract of Z. album showed a significant inhibition in the NLRP3 inflammasome pathway and significantly downregulated NLRP3 , TXNIP and caspase-1 expression, along with reduced levels of IL-1β and IL-18. Indeed, NLRP3 inflammasome inactivation has been reported to be a potential mechanism of action of various compounds found in Z. album extract [ 71 , 72 , 73 , 74 , 75 ]. A better outcome has been observed with aerial part extract than the root extract.…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggested that circ_DLGAP4 might inactivate the NF-κB pathway to inhibit OGD/R-induced microglia M1 polarization and proinflammatory cytokine production, but promote microglia M2 polarization and anti-inflammatory cytokine production. However, according to previous studies, PMA is an NF-κB pathway activator, as well as a microglia M1 polarization stimulator (Jin et al 2021;Kushwah et al 2022;Lei et al 2023). Therefore, the reversal of circ_DLGAP4' impact on microglia polarization and inflammatory cytokine production by PMA might not be exclusively attributed to the activation of the NF-κB pathway.…”
Section: A C C E P T E Dmentioning
confidence: 93%
“…NF-κB can promote the transcription of NLRP3, leading to the occurrence of pyroptosis [17]. NF-κB is involved in the pathophysiology of various central nervous system diseases, including epilepsy [18] and brain hemorrhage [19]. However, whether IRAK4 in epilepsy can act through the activation of the NF-κB/NLRP3 pathway is still unknown.…”
Section: Introductionmentioning
confidence: 99%